2016
DOI: 10.1002/oby.21481
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of portion‐controlled prepackaged foods to promote weight loss

Abstract: Objective Providing portion-controlled prepackaged foods in a behavioral counseling intervention may promote more weight and fat loss than a standard self-selected diet. Methods: The primary aim was to test whether providing portion-controlled prepackaged lunch and dinner entrées within a behavioral weight loss intervention promotes greater weight loss at 12 weeks in overweight/obese adults compared to self-selected foods. Other aims were to examine effects on biological factors, fitness, and meal satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The data from the present study are generally consistent with previous research showing that provision of portioned controlled foods as a dietary intervention for weight loss is an effective approach compared to conventional diets ( 5 8 , 21 23 ). For example, a 2003 meta-analysis of six randomized controlled trials found that 3-month weight loss in participants consuming a partial meal replacement diet exceeded that of participants consuming a standard reduced calorie diet by 2.5–3.0 kg (~7% change from baseline) ( 5 ).…”
Section: Discussionsupporting
confidence: 91%
“…The data from the present study are generally consistent with previous research showing that provision of portioned controlled foods as a dietary intervention for weight loss is an effective approach compared to conventional diets ( 5 8 , 21 23 ). For example, a 2003 meta-analysis of six randomized controlled trials found that 3-month weight loss in participants consuming a partial meal replacement diet exceeded that of participants consuming a standard reduced calorie diet by 2.5–3.0 kg (~7% change from baseline) ( 5 ).…”
Section: Discussionsupporting
confidence: 91%
“…Firstly, based on the design of the current trial, it was not feasible to blind participants and provider, which is common in trials of such nature [9,10]. Additionally, recent evidence demonstrates that pre-prepared meals result in greater weight and fat loss than a standard self-selected diet [61]. However, due to feasibility reasons, this study was only able to provide the pre-prepared meals to the experimental condition (EX-LC).…”
Section: Limitations and Issues Of Concernmentioning
confidence: 99%
“…In two recent weight loss studies, portion control strategies (including provision of pre‐portioned meals) as part of a 12‐week (Rock et al . ) or a 12‐month (Rolls et al . ) weight loss trial facilitated early weight loss.…”
Section: Long‐term Impact Of Large Portions On Weight Gainmentioning
confidence: 99%
“…Also, it relieves the consumer from having to work out amounts to prepare and serve. In two recent weight loss studies, portion control strategies (including provision of pre-portioned meals) as part of a 12-week (Rock et al 2016) or a 12-month (Rolls et al 2017) weight loss trial facilitated early weight loss. However, in the 12-month trial, portion control strategies did not lead to a greater weight loss than standard advice.…”
Section: Long-term Impact Of Large Portions On Weight Gainmentioning
confidence: 99%